Comparing Prednisone and Methotrexate to Off-label Biologic Infliximab for Management of Ocular Uveitis: A Cost-minimization Analysis - William V. Padula; Miguel Cordero-Coma; Taygan Yilmaz; William V. Padula; Michéal J. Gallagher; Jonathan D. Campbell (Journal of Health Economics and Outcomes Research)
**Background:** Approximately 3.75% of cases of blindness in the United States are caused by uveitis. Incurred clinical costs and lost productivity related to vision loss in these cases totals $3.58 billion annually.